Contribution of coated humic acids calculated through their surface coverage on nano iron oxides for ofloxacin and norfloxacin sorption. (September 2015) - Peng, Hongbo; Liang, Ni; Li, Hao; Chen, Fangyuan; Zhang, Di; Pan, Bo; Xing, Baoshan
Abstract: Sorption of organic contaminants on organo-mineral complexes has been investigated extensively, but the sorption contribution of mineral particles was not properly addressed before calculating K OC, especially for ionic organic contaminants. We measured the surface coverage of a humic acid (HA) on nano iron oxides (n-Fe2 O3 ) in a series of synthesized organo-mineral complexes. The contribution of the coated HA to ofloxacin (OFL) and norfloxacin (NOR) sorption in HA–n-Fe2 O3 complexes was over 80% of the total sorption with the surface coverage of 36% and f OC of 1.6%. All the coated HA showed higher sorption to NOR and OFL in comparison to the original HA, suggesting HA fractionation and/or physical re-conformation during organo-mineral complex formation. The decreased K OC with multilayer coating may suggest the importance of site-specific interactions for OFL sorption, while the increased K OC with multilayer coating may suggest the importance of partitioning in hydrophobic region for NOR sorption. Highlights: The sorption of nano iron oxides was calculated through their exposed surface area. The contribution of the coated HA was over 80% of the total sorption. The decreased K OC with multilayer coating suggests site-specific sorption for OFL. The increased K OC with multilayer coating suggests NOR partitioning in hydrophobic region. Abstract : Coated humic acid showed increased sorption to ionic organic contaminants in comparison to bulk humic acid, and accounted for over 80% of the total sorption at f OC of 1.6%.